1999
DOI: 10.1007/s004250050618
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of the gene for chimeric calcium/calmodulin-dependent protein kinase in anthers

Abstract: Chimeric Ca(2+)/calmodulin-dependent protein kinase (CCaMK) was cloned from developing anthers of lily (Lilium longiflorum Thumb. cv. Nellie White) and tobacco (Nicotiana tabacum L. cv. Xanthi). Previous biochemical characterization and structure/function studies had revealed that CCaMK has dual modes of regulation by Ca(2+) and Ca(2+)/calmodulin. The unique structural features of CCaMK include a catalytic domain, a calmodulin-binding domain, and a neural visinin-like Ca(2+)-binding domain. The existence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 48 publications
1
35
0
1
Order By: Relevance
“…harvard.edu/tgi), from which two of the six ESTs in TC290169 were from flower tissue, while the remaining four came from root tissue. The higher level expression of OsDMI3 in flower organs was in contrast to the expression pattern reported in M. truncatula (Levy et al, 2004), but consistent with that observed for the CCaMK genes in non-legumes such as lily (Lilium longiflorum) and tobacco (Nicotiana tabacum; Poovaiah et al, 1999). The expression level of OsDMI3 in rice roots was not significantly affected by mycorrhization (Fig.…”
Section: Features Of Osdmi3supporting
confidence: 88%
“…harvard.edu/tgi), from which two of the six ESTs in TC290169 were from flower tissue, while the remaining four came from root tissue. The higher level expression of OsDMI3 in flower organs was in contrast to the expression pattern reported in M. truncatula (Levy et al, 2004), but consistent with that observed for the CCaMK genes in non-legumes such as lily (Lilium longiflorum) and tobacco (Nicotiana tabacum; Poovaiah et al, 1999). The expression level of OsDMI3 in rice roots was not significantly affected by mycorrhization (Fig.…”
Section: Features Of Osdmi3supporting
confidence: 88%
“…This result supports the view that CaM binding to CaMBD is required for the negative regulation of CCaMK. It has also been reported that lily and tobacco (Nicotiana tabacum) CCaMKs are expressed in anthers (Patil et al, 1995;Liu et al, 1998;Poovaiah et al, 1999), and increased expression of both CCaMK and CaM were detected in pollen cells of tobacco (Poovaiah et al, 1999). These results imply the possibility that nonleguminous CCaMKs are also involved in reproductive stages in which CCaMK and CaM interaction is required.…”
Section: Contrasting Roles Of Cam Binding For Endosymbiont Accommodationmentioning
confidence: 71%
“…Based on the characterization of CCaMK, including in vitro phosphorylation and ligand binding assays with a CCaMK deletion series, a working model for CCaMK activation has been proposed (Sathyanarayanan et al, 2000). Additional studies have been made of the biochemical and expression properties of CCaMK proteins in nonlegumes (Liu et al, 1998;Poovaiah et al, 1999;Pandey and Sopory, 2001); however, the detailed mechanism of CCaMK activation in response to cytosolic Ca 2+ signals remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco (Nicotiana tabacum) CCaMK was indicated to play a role in controlling the development of anther (Poovaiah et al, 1999), and pea (Pisum sativum) CCaMK was up-regulated in roots in response to low temperature and salt treatment (Pandey et al, 2002). Recent results showed that CCaMK from maize (Zea mays; ZmCCaMK) and rice (OsCCaMK) both play important roles in abscisic acid-induced antioxidant protection (Ma et al, 2012;Shi et al, 2012).…”
Section: +mentioning
confidence: 99%